The biodiscovery potential of marine bacteria: an investigation of phylogeny and function. Issue 4 (4th April 2013) - Mühling, Martin; Joint, Ian; Willetts, Andrew J.
Summary A collection of marine bacteria isolated from a temperate coastal zone has been screened in a programme of biodiscovery. A total of 34 enzymes with biotechnological potential were screened in 374 isolates of marine bacteria. Only two enzymes were found in all isolates while the majority of enzyme activities were present in a smaller proportion of the isolates. A cluster analysis demonstrated no significant correlation between taxonomy and enzyme function. However, there was evidence of co‐occurrence of some enzyme activity in the same isolate. In this study marine Proteobacteria had a higher complement of enzymes with biodiscovery potential than Actinobacteria; this contrasts with the terrestrial environment where the Actinobacteria phylum is a proven source of enzymes with important industrial applications. In addition, a number of novel enzyme functions were more abundant in this marine culture collection than would be expected on the basis of knowledge from terrestrial bacteria. There is a strong case for future investigation of marine bacteria as a source for biodiscovery.